General properties of Bertrand curves in Riemann-Otsuki space - Yilmaz, Muenevver Yidirim; Bektas, Mehmet (Pergamon-Elsevier Science Ltd, 2008)
In this paper we studied the general properties of Bertrand curves and their characterizations in Riemann-Otsuki space. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Riemann-Otsuki spaces; Frenet formula; Bertrand curve